2020
DOI: 10.1128/mbio.00142-20
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Polyomavirus DNA Replication Induces Senescence in Human Dermal Fibroblasts in a Kap1/Trim28-Dependent Manner

Abstract: Merkel cell polyomavirus (MCPyV) is the only polyomavirus known to be associated with tumorigenesis in humans. Similarly to other polyomaviruses, MCPyV expresses a large tumor antigen (LT-Ag) that, together with a small tumor antigen (sT-Ag), contributes to cellular transformation and that is of critical importance for the initiation of the viral DNA replication. Understanding the cellular protein network regulated by MCPyV early proteins will significantly contribute to our understanding of the natural MCPyV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…The biological relevance of this finding has been validated in an in vivo model, where the induction of genotoxicity and consequent senescence by the administration of bleomycin reduces viral recovery from the lungs of VSV-infected mice 6 days post-infection [85]. Similarly, the infection of human primary dermal fibroblasts with the double stranded DNA merkel cell polyoma virus (MCPyV) activates the ATM-dependent DDR response and KAP1-dependent senescence, resulting in a significant reduction of the viral replication rate [86].…”
Section: Viral Infectionsmentioning
confidence: 86%
“…The biological relevance of this finding has been validated in an in vivo model, where the induction of genotoxicity and consequent senescence by the administration of bleomycin reduces viral recovery from the lungs of VSV-infected mice 6 days post-infection [85]. Similarly, the infection of human primary dermal fibroblasts with the double stranded DNA merkel cell polyoma virus (MCPyV) activates the ATM-dependent DDR response and KAP1-dependent senescence, resulting in a significant reduction of the viral replication rate [86].…”
Section: Viral Infectionsmentioning
confidence: 86%
“…Expression of the large T antigen of MCPyV has been demonstrated to induce DSB, the activation of ataxia–telangiectasia mutated (ATM) protein kinase and the phosphorylation of p53 and KRAB-associated protein 1 (KAP-1). The accumulation of phosphorylated KAP-1 has been associated with a G2 phase arrest, a mechanism that may avoid viral DNA replication [ 24 , 25 ].…”
Section: Virus and Senescencementioning
confidence: 99%
“…Finally, a negative role of senescence on MCPyV infection has been reported. Siebels et al (2020) demonstrated that KAP-1 is a restriction factor for MCPyV infection and that replication of the virus induces the phosphorylation of KAP-1 and the subsequent cellular senescence [ 25 ]. Therefore, it has been proposed that senescence is a host defense mechanism against MCPyV [ 25 ].…”
Section: Virus and Senescencementioning
confidence: 99%
“…MCPyV was able to exploit these senescent cells by maintaining its viral genome for long-term survival (Figure 6f). MCPyV-induced senescence was recently reported by Siebels et al 45 . Although their MCPyV LT interaction study revealed an interaction with KRAB-associated protein 1 (KAP1), a senescence-related factor 46 in primary normal human dermal fibroblasts (nHDF), it was not clear if LT expression alone is sufficient to induce host cellular senescence.…”
Section: Discussionmentioning
confidence: 70%